Did the flowering of the La Tolita culture 3000 BP result from a natural disaster? - Jean François Dumont (Unité Mixte de Recherche 8504 Géographie-cités, 2010)
The La Tolita site appeared on the Pacific coast of northern Ecuador around 3000 BP, and its culture quickly spread throughout the interior alluvial plain of mangrove and thick rainforest vegetation up to an elevation of 2000m along the Andean slopes. New geomorphic evidence shows that the flowering of the La Tolita culture could have followed a natural disaster that opened a new waterway, which facilitated communication with gold bearing areas and Andean communities landward. The La Tolita area is located in the Esmeraldas-Tumaco seismic zone, one of the most active on earth. The channel avulsion is correlated with active fault motion in the alluvial lowlands of the Santiago and Cayapas River basins. We question here the relation between the two following phenomenons, natural disaster and cultural flowering.